2023
DOI: 10.3390/app13074188
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Expanded Glass and Crushed Expanded Polystyrene on the Performance Characteristics of Lightweight Concrete

Abstract: This paper describes the production and performance characteristics of lightweight concrete (LWC) made from porous aggregates, such as expanded glass (EG), made from glass waste, and crushed expanded polystyrene waste (CEPW), obtained by crushing packaging waste from household appliances and ordinary Portland cement (OPC). During the study, the LWC density, thermal conductivity, compressive strength, bending strength, water absorption, deformations, composite structure, and freeze–thaw resistance were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Currently, expanded polystyrene (EPS) is a widely used material in structures due to its rational properties, such as lightness, low thermal conductivity, moisture resistance, good chemical resistance, convenient processing, and low cost [16][17][18]. The studies have shown that recycled EPS waste, as well as manufactured EPS beads can be used as an aggregate for the development of lightweight cement-based thermal insulation composites [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, expanded polystyrene (EPS) is a widely used material in structures due to its rational properties, such as lightness, low thermal conductivity, moisture resistance, good chemical resistance, convenient processing, and low cost [16][17][18]. The studies have shown that recycled EPS waste, as well as manufactured EPS beads can be used as an aggregate for the development of lightweight cement-based thermal insulation composites [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Water absorption increased by 44.8% (from 5.7 to 8.3%). A previous study [19] examined the effect of LWA (EG and EPS) on composite properties. Using the EPS aggregate, the amount of deformation of the lightweight composite was reduced while the durability was increased.…”
Section: Introductionmentioning
confidence: 99%
“…The core of the foaming method is the use of blowing agents, which can be chemical blowing agents or physical blowing agents. Chemical blowing agents create air bubbles in the concrete, while physical blowing agents introduce air bubbles through mechanical action [ 8 , 9 ]. Foamed lightweight concrete has advantages such as lightness, insulation, and environmental friendliness, but it also has disadvantages, such as a low compressive strength and uneven density [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%